Implementation of Government Policies Regarding the Full Day School Program in the New Normal - Utomo, Santri Prabowo; Gunarhadi, Gunarhadi; Sukarno, Sukarno (LPPM Undiksha, 2021)
Changes in government policies in the education sector are to prevent the spread of Covid-19. This study aims to explore the results of changes in the learning process of a full-day school. The method used is descriptive qualitative with a case study. Data collected by observation, interview, questionnaire filling, and documentation. Data analysis using interactive qualitative by Miles and Huberman. The results in this study describe the school preparation in implementing changes in government policy about the learning process in a full-day school program during the New Normal. The learning can be well implemented with some development of the school itself following the New Normal Era health protocol in achieving educational goals. The learning in school can be carried out if there are careful preparation and discipline in applying it so the learning can be safely for school residents. The implementation of several changes to health regulations and protocols encourages the emergence of social distancing behavior and minimizes the possibility of a crowd in the school community.